2022
DOI: 10.1155/2022/9631858
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Application of Restrictive Brace Combined with Psychological Intervention after Replantation of Severed Fingers in Children

Abstract: Objective. After replantation of severed fingers in infants, the utility model patent upper limb restrictive brace-assisted bed rest braking, combined with psychological intervention, can alleviate children’s anxiety, so as to reduce the occurrence of vascular crisis. Methods. The study period was from April 2015 to July 2018. In this paper, 30 children with finger injuries in hand surgery in the CIS electronic medical record system of Cangzhou Integrated Traditional Chinese and Western Medicine Hospital were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…8–28 The timeframe of patient recruitment in included studies ranged from 1973 to 2020, where 13 studies included patients who were recruited before the year 2000, 8–12,15,17,20,21,23,25,27,28 and 10 studies recruited patients who were recruited onwards of the year 2000 (Table 1). 10,13,14,16,18,19,22,24,26,27 The mean age of patients across included studies ranged from 1.3 to 11.7 years old. The proportion of male patients across included studies ranged from 46% to 87%; hence, the proportion of female patients ranged from 13% to 54%.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…8–28 The timeframe of patient recruitment in included studies ranged from 1973 to 2020, where 13 studies included patients who were recruited before the year 2000, 8–12,15,17,20,21,23,25,27,28 and 10 studies recruited patients who were recruited onwards of the year 2000 (Table 1). 10,13,14,16,18,19,22,24,26,27 The mean age of patients across included studies ranged from 1.3 to 11.7 years old. The proportion of male patients across included studies ranged from 46% to 87%; hence, the proportion of female patients ranged from 13% to 54%.…”
Section: Resultsmentioning
confidence: 99%
“…7 Dec postulated that this may be due to adult male patients experiencing severe mechanisms of injury associated with digit amputation more frequently, 7 whereas this difference between sexes may not occur in children. 22 3.55 Across included studies on successful pediatric digit replantations, we found that reporting of patient-reported outcomes after replantation was limited. In particular, no studies reported outcomes using the Disabilities of the Arm, Shoulder, and Hand questionnaire.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations